Design Thinking Testing of AR/VR Application for Bali's Lontar Prasi Preservation - Christina Purnama Yanti; I Gede Iwan Sudipa; Putu Wirayudi Aditama (Jurnal Multidisiplin Madani, 2023)
This study investigates the use of Design Thinking in the creation of Augmented Reality (AR) and Virtual Reality (VR) applications for the preservation of Bali's Lontar Prasi cultural heritage. As a piece of Indonesian cultural patrimony, Lontar Prasi necessitates a novel approach to its preservation in the digital age. This research identifies UI/UX issues of AR/VR applications based on user problems through the phases of Emphasis, Definition, Ideation, Prototype, and Test. Changes were made to the icon display, 3D character information, and UI positioning as a result. With an average score of 80 (Excellent) on the System Usability Scale (SUS), testing revealed a substantial improvement in user satisfaction. These results demonstrate that the Design Thinking methodology is effective for addressing UI/UX issues and enhancing the app's acceptability. In conclusion, this approach can serve as a foundation for future advancements in the preservation of cultural heritage using modern technology for digitized cultural heritage